Adverse Childhood Experiences and Blood Pressure Trajectories From Childhood to Young Adulthood. Issue 19 (12th May 2015) - Su, Shaoyong; Wang, Xiaoling; Pollock, Jennifer S.; Treiber, Frank A.; Xu, Xiaojing; Snieder, Harold; McCall, W. Vaughn; Stefanek, Michael; Harshfield, Gregory A.
<x xml:space="preserve">Abstract</x> Background— The purposes of this study were to assess the long-term effect of adverse childhood experiences (ACEs) on blood pressure (BP) trajectories from childhood to young adulthood and to examine whether this relation is explained by childhood socioeconomic status (SES) or risk behaviors that are associated with ACEs. Methods and Results— Systolic and diastolic BPs were measured up to 16 times (13 times on average) over a 23-year period in 213 African Americans and 181 European Americans 5 to 38 years of age. Retrospective data on traumatic experiences before 18 years of age were collected, including abuse, neglect, and household dysfunction. Individual growth curve modeling within a multilevel framework was used to examine the relation between exposure to ACEs and BP development. No main effect of ACEs on average BP levels was found. However, a significant interaction of ACE score with age3 was observed (systolic BP, P=0.033; diastolic BP, P=0.017). Subjects who experienced multiple traumatic events during childhood showed a faster rise in BP levels after 30 years of age than those without ACEs. As expected, a graded association of ACEs with childhood socioeconomic status and negative health behaviors was observed (P<0.001). The ACE–systolic BP relation was not explained by these factors, whereas the ACE–diastolic BP relation was partially mediated by illicit drug use. Conclusion— In this novel longitudinal study, we observed that participants who were exposed to multiple ACEs displayed a greater increase in BP levels in young adulthood compared with their counterparts without ACEs.